Ischemic preconditioning boosts post-exercise but not resting cardiac vagal control in endurance runners - Sabino-Carvalho, J. L.; Obeid-Freitas, T.; Paula-Ribeiro, M.; Lopes, T. R.; Ferreira, T. H. N.; Succi, J. E.; Silva, A. C.; Silva, B. M. (European Journal of Applied Physiology, 2019)
Purpose: High cardiac vagal control in endurance athletes has been generally associated with adequate recovery from training and readiness to cope high-intensity training. A method that improves cardiac vagal control in endurance athletes could therefore be advantageous. Accordingly, we sought to test whether ischemic preconditioning (IPC) could enhance cardiac vagal control in endurance runners. Methods: Fifteen subjects underwent IPC, sham ultrasound (SHAM) or control (CT), in random order. Subjects were informed both IPC and SHAM would be beneficial vs. CT (i.e., similar placebo induction), and IPC would be harmless despite ischemia sensations (i.e., nocebo avoidance). Resting cardiac vagal control was assessed via respiratory sinus arrhythmia (RSA) and heart rate variability (HRV) indexes. Post-exercise cardiac vagal control was assessed via heart rate recovery [HR time constant decay (T30) and absolute HR decay (HRR30s)] during 30-s breaks of a discontinuous incremental test. Capillary blood samples were collected for lactate threshold identification. Results: RSA and HRV were similar among interventions at pre- and post-intervention assessments. Lactate threshold occurred at 85 ± 4% of maximal effort. T30 was similar among interventions, but IPC increased HRR30s at 70% and 75% of maximal effort vs. SHAM and CT (70%: IPC = 31 ± 2 vs. SHAM = 26 ± 3 vs. CT = 26 ± 2 bpm, mean ± SEM, P < 0.01; 75%: IPC = 29 ± 2 vs. SHAM = 25 ± 2 vs. CT = 24 ± 2 bpm, P < 0.01). Conclusion: IPC did not change resting cardiac vagal control, but boosted fast post-exercise cardiac vagal reactivation at exercise intensities below lactate threshold in endurance runners.